Kierownictwo Polskiej Zjednoczonej Partii Robotniczej w latach 1986–1990. Szkic do portretu - Szumiło, Mirosław (Pamięć i Sprawiedliwość, 2011)
The PUWP leadership in the years 1986–1990: A sketch for a portraitActual power in the Polish United Workers’ Party (PUWP) was held by thesocalled leadership, i.e. members of the Political Bureau and the Secretariat of the Central Committee (CC). The Political Bureau formulated the party policy and made strategic decisions, while the Secretariat managed the day-to-day operations of the party apparatus. Due to the presence of workers’ representatives within the Political Bureau, and the participation in its meetings of large numbers of invited guests, in the years 1986-1990 the Political Bureau turned into a discussion forum. The real center of decision-making was located in the informal circle closest to the first secretary of the PUWP CC, Wojciech Jaruzelski.In the period under discussion, 35 real members of the power apparatus and 7 figureheads formed part of the Political Bureau and CC Secretariat. The greatest personnel changes in the membership of both organs of power took place on the eve of the “round table” discussions, in December 1988. The following criteria can be considered as key for promoting new people to the leadership of the PUWP: organizing skills, experience in leadership positions, specialized education, negotiation skills, and public speaking skills. But above all, those selected were people who could be trusted.Between 1986 and 1990, the PUPW leadership was very diverse in terms of origin, generational experience, and career paths. It included representatives of four (idea-based) generations of party activists. The oldest, those of the “wartime generation,” had joined the communist movement in the Polish Army during the last years of World War II. The so-called “zetempowcy,” who had been active in the Association of Polish Youth at the turn of the 1940s and 1950s before joining the PUWP, were the largest group. Representatives of the “Gomułka generation” had joined the party in the 1960s. The two youngest leaders belonged to the “Gierek generation” and had started their political careers in the 1970s.